David Baldus and the Legacy of McCleskey v. Kemp - Gross, Samuel R. (2012)
The first major empirical challenge to racial discrimination in the use of the death penalty in the United States was presented in federal court in the case of William L. Maxwell, who was sentenced to death in Arkansas in 1962 for the crime of rape.1 It was based on a landmark study by Marvin Wolfgang, a distinguished criminologist who had collected data on some 3000 rape convictions from 1945 through 1965 in selected counties across eleven southern states.2 He found that black men who were convicted of rape were seven times more likely to be sentenced to death than white men, and that black men who were convicted of raping white women were eighteen times more likely to be sentenced to death than men convicted of rape in any other racial combination.3 Wolfgang also examined other variables and found that the only one that was strongly related to death sentencing—the commission of a contemporaneous felony—did not explain these racial patterns.